Bilateral simultaneous neck of femur fractures from a single injury in a high-risk patient - Roy, Mainak; Das, Deepanjan; Bhavani, Prashant; Dwidmuthe, Samir; Sah, Saurabh; Sadar, Amey S. (International Journal of Research in Orthopaedics, 2024)
Simultaneous bilateral neck of femur fractures resulting from a single traumatic event are exceptionally rare. Often these patients have underlying metabolic bone disorders like renal osteodystrophy, osteomalacia, long term steroid intake, osteoporosis, hyperparathyroidism etc. We present a unique case of bilateral neck femur fractures in a patient with no history or objective proof of metabolic bone disease. This case underscores the significance of recognizing atypical presentations and the need for individualized management. A 70-year-old male patient presented with altered sensorium, disorientation, and bilateral hip fractures following a self-fall at home. The absence of metabolic bone abnormalities, along with pre-existing systemic hypertension and coronary artery disease, made this presentation remarkable. Diagnostic workup revealed hyponatremic encephalopathy, further complicating the high-risk surgical status of the patient. A two-stage approach with bipolar uncemented hemiarthroplasty was chosen, and early mobilization was initiated. Remarkably, the patient returned to pre-injury mobility soon after surgery, illustrating the successful outcome. This case highlights the rarity of simultaneous bilateral neck of femur fractures in patients even without metabolic bone disease, emphasizing the need for careful evaluation and customized management. The collaborative efforts of surgeons, physicians, and anesthetists were pivotal in achieving a positive outcome, demonstrating the remarkable potential of multidisciplinary teamwork in challenging medical scenarios. This case serves as a testament to the dedication and expertise of the medical community in the face of extraordinary challenges.